APPLICATION OF PRINCIPLES OF DESIGNING OF HEURISTIC SYSTEMS OF SUPERVISION IN TECHNOLOGIES OF TECHNICAL DIAGNOSTICS - Golub, Sergey (Proceedings of National Aviation University (archive), 2006)
The principles of planning of the heuristic supervision systems are expounded and the process of their application in technologies of technical diagnostics is described. It is suggested to use the Heuristic Supervision systems as a basis for designing of process of diagnostics of technical objects.